ANALISIS SISTEM AKUNTANSI PENGGAJIAN DALAM RANGKA MENINGKATKAN PENGENDALIAN INTERN PADA PT. SARANA SULUT VENTURA - Jones, Jeni; Karamoy, Herman; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Payroll accounting system is a group of human resources and equipment designed to process company data in the form of information. The purpose of this study is to analyze the application of a payroll accounting system to internal control at PT Sarana Sulut Ventura with descriptive qualitative method. This study finds that the documents and records are good, but the functions, procedures, and internal control are not good. This result indicates that the payroll accounting system applied at PT Sarana Sulut Ventura has not been good and is not in accordance with generally accepted theories. This has an impact on the internal control system applied at PT Sarana Sulut Ventura, which is also inadequate because it does not meet the components of good internal control.